Spatial and Motor Aspects in the “Action-Sentence Compatibility Effect” - Greco, Alberto (Frontiers in Psychology, 2021)
The Action-sentence Compatibility Effect (ACE) is often taken as supporting the fundamental role of the motor system in understanding sentences that describe actions. This effect would be related to an internal “simulation,” i.e. the reactivation of past perceptual and motor experiences. However, it is not easy to establish whether this simulation predominantly involves spatial imagery or motor anticipation. In the classical ACE experiments, where a real motor response is required, direction and motor representations are mixed. In order to disentangle spatial and motor aspects involved in the ACE, we performed six experiments in different conditions, where the motor component was always reduced, asking participants to judge the sensibility of sentences by moving a mouse, thus requiring a purely spatial representation, compatible with nonmotor interpretations. In addition, our experiments had the purpose of taking into account the possible confusion of effects of practice and of compatibility (i.e. differences in reaction times simultaneously coming from block order and opposite motion conditions). Also, in contrast to the usual paradigm, we included no-transfer filler sentences in the analysis. The ACE was not found in any experiment, a result that failed to support the idea that the ACE could be related to a simulation where spatial aspects rather than motor ones prevail. Strong practice effects were always found and were carved out from results. A surprising effect was that no-transfer sentences were processed much slower than others, perhaps revealing a sort of participants’ awareness of the structure of stimuli, i.e. their finding that some of them involved motion and others did not. The relevance of these outcomes for the embodiment theory is discussed.